Susceptibility of pear cultivars to entomosporiosis - Marchi, Thiago; Ribeiro Oliari, Ires Cristina; Oliveira, Anna Claudia; Maia, Aline José; Piva, Rafael; Vasconcelos Botelho, Renato (Comunicata Scientiae, 2018)
The entomosporiosis is considered a major disease of pear in Brazil, one of the most responsible for premature defoliation in plants. The objective of this study was to characterize the susceptibility of pear tree cultivars Housui, Cascatense, Packam’s Triumph and Rocha for the intensity of leaf spot entomosporiosis. The experiment was conducted at the experimental orchard of the State University of the Midwest (Unicentro), Paraná State, Guarapuava County, Brazil during the 2013/2014 season. The incidence and severity were monitored during 77 days from the beginning of the symptoms in 25 leaves of 8 plants per cultivar. With these data the following variables were calculated: early onset of symptoms (EOS), maximum incidence and severity (Imax and Smax) and the Area Under the Incidence Progress Curve (AUIPC) and Severity (AUSPC). In addition, the data were checked for severity and the best adjustments for the monomolecular, logistic and exponential models were tested. From these results it is clear that all the studied cultivars are susceptible to leaf spot entomosporiosis, however, Housui pear cultivar presented higher endurance while Rocha and Cascatense cultivars presented greater susceptibility to this disease.